L’intimité, la fiabilité et les paroles des femmes : quand les violences conjugales rencontrent les institutions - Alessandra Gribaldo (Archivio Antropologico Mediterraneo)
In this article I wish to analyze the conundrums arising when battered women's words meet institutions and law. In the context of intimate partner violence documentary evidence is often not available and women’s testimonies play an essential role. Pressing charges and speaking out means taking the floor as a legal subject in order to demand justice and to speak in legal terms has a decisive, effective and symbolic value in the definition of victimhood. Nonetheless the pressure on the victim to speak about the factual events, about herself and her relationship with the perpetrator and to denounce him before the law has vast implications. Drawing on a research carried out in Italy, I reflect on how violence in intimate relationships can be made present to the institutions and how the abused subject is constituted in front of them. Self-governance and reflexivity make testimony intelligible and legally significant and make women reliable victims. Yet paradoxically violence exerted in an intimate relationship does not easily provide for such a perfect victim: this reliable subject that institutions require does not match women's experiences, stances, decisions, hesitations.